Systematic conservation planning for intraspecific genetic diversity - Paz-Vinas, Ivan (Proc Biol Sci, 2018)
Intraspecific diversity informs the demographic and evolutionary histories of populations, and should be a main conservation target. Although approaches exist for identifying relevant biological conservation units, attempts to identify priority conservation areas for intraspecific diversity are scarce, especially within a multi-specific framework. We used neutral molecular data on six European freshwater fish species (Squalius cephalus, Phoxinus phoxinus, Barbatula barbatula, Gobio occitaniae, Leuciscus burdigalensis and Parachondrostoma toxostoma) sampled at the riverscape scale (i.e. the Garonne-Dordogne river basin, France) to determine hot- and coldspots of genetic diversity, and to identify priority conservation areas using a systematic conservation planning approach. We demonstrate that systematic conservation planning is efficient for identifying priority areas representing a predefined part of the total genetic diversity of a whole landscape. With the exception of private allelic richness (PA), classical genetic diversity indices (allelic richness, genetic uniqueness) were poor predictors for identifying priority areas. Moreover, we identified weak surrogacies among conservation solutions found for each species, implying that conservation solutions are highly species-specific. Nonetheless, we showed that priority areas identified using intraspecific genetic data from multiple species provide more effective conservation solutions than areas identified for single species or on the basis of traditional taxonomic criteria.